Triglyceride-glucose index predicts death in patients with stroke younger than 65 - Liu, Ruishan; Li, Lijuan; Wang, Lu; Zhang, Shihong (Frontiers in Neurology, 2023)
Background The triglyceride-glucose index (TGI), a reliable surrogate indicator of insulin resistance (IR), has been proven to be a predictor of the incidence of ischemic stroke. The role of TGI in predicting the outcomes of stroke patients remains controversial. Susceptibility to IR-related diseases varies among patients of different ages. The study aims to evaluate the predictive value of TGI levels on clinical outcomes of patients with ischemic stroke of different ages. Method This was a retrospective cohort study including patients with ischemic stroke in the Department of Neurology at West China Hospital. TGI was calculated as ln [fasting triglyceride (mg/dL) × fasting glucose (mg/dL)/2]. The patients were subdivided into 3 tertiles according to TGI levels. Multivariate logistic regression analyses were conducted to estimate the association between TGI levels and post-stroke outcomes among the whole patients, younger patients (<65), and older patients (>=65). The outcomes included death and unfavorable functional outcome (modified Rankin scale score 3–6) at 3 and 12 months after stroke. Results A total of 3,704 patients (men, 65.08%, mean age, 61.44 ± 14.15; women 34.92%, mean age, 65.70 ± 13.69) were enrolled in this study. TGI levels were not associated with 3 month or 12 month death in the whole patients. Patients with higher TGI levels (T2 and T3) had a higher risk of 3 month death than those had lower TGI levels (T1) in the younger group (T2 vs. T1: OR 2.64, 95% CI 1.03–6.79, p = 0.043; T3 vs. T1: OR 2.69, 95% CI 1.00–7.10, p = 0.049) but not in the older group. Additionally, Kaplan–Meier estimate analysis illustrated that the 12 month death risk was significantly higher in the group with the highest TGI among younger patients (p for log-rank test = 0.028) but not among older patients. There was an interactive effect between TGI and age on 3 month death (p for interaction = 0.013) and 12 month death (p for interaction = 0.027). However, TGI was not associated with unfavorable functional outcome at 3 month or 12 month after stroke. Conclusion Elevated TGI independently predicts death at 3 months and 12 months in patients under 65 with ischemic stroke. Regulating TGI is expected to be an approach to enhance prognosis in young individuals affected by ischemic stroke.